How Perceived Organizational Support Impact Teacher Engagement: The Key Role of Job Satisfaction - hidayati, nurul; Lubis, Rahmi; Turnip, Kaiman (Journal of Educational, Health and Community Psychology, 2025)
This study aims to investigate the role of perceived organizational support, on the dependent variable, work engagement, mediated by job satisfaction among teacher. The research design employed is characterized as explanatory quantitative research. A cluster random sampling technique was utilized for the selection of participants. The sample size for this investigation comprised 300 teachers. Data analysis was conducted using Smart-PLS in conjunction with the Structural Equation Modeling (SEM) methodology. The findings of this research reveal a significant relationship between perceived organizational support and work engagement among teacher, as well as a notable impact of perceived organizational support on the job satisfaction of these educators; additionally, a significant effect of job satisfaction on work engagement was identified, alongside the mediating role of job satisfaction in the relationship between perceived organizational support and work engagement among teachers.